2018
DOI: 10.3892/etm.2018.5739
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of vitamin D receptor with bronchial asthma in children

Abstract: This study was designed to investigate the correlation of vitamin D receptor (VDR) gene polymorphism with bronchial asthma in children. Seventy patients admitted to Daqing Longnan Hospital and diagnosed as bronchial asthma for the first time from April 2015 to May 2017 were selected as observation group. Patients received routine treatment and intervention. Seventy healthy subjects admitted to hospital during the same period were enrolled as the control group. Vitamin D gene polymorphism was detected by polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
0
16
1
1
Order By: Relevance
“…In the present study, we found no significant association between FEV1 values and VDR gene polymorphisms or serum 25(OH)VD levels. These findings regarding FEV1 values are in disagreement with previously published findings . One possible explanation for these discrepancies is that all patients with asthma included in the present study had severe bronchial asthma.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, we found no significant association between FEV1 values and VDR gene polymorphisms or serum 25(OH)VD levels. These findings regarding FEV1 values are in disagreement with previously published findings . One possible explanation for these discrepancies is that all patients with asthma included in the present study had severe bronchial asthma.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, VDR rs2228570 was also a risk factor for childhood asthma susceptibility in dominant (OR = 1.281, 95% CI = 1.055‐1.555, P = .012) and allele (OR = 1.591, 95% CI = 1.052‐2.405, P = .028) models in Caucasian patients. In contrast, Hou et al did not find any correlation between VDR rs1544410 with childhood bronchial asthma. In our study, no association was found between VDR rs1544410 loci with asthma susceptibility in the Kurdish population.…”
Section: Discussionmentioning
confidence: 80%
“…As both had similar ethnic population the difference in age group of the population could be attributed as the reason for this variation. Interestingly study done by Wjst et al done in Germany [ 16 ] had found no association in family transmission [ 12 , 25 , 27 , 28 , 29 , 31 , 32 , 33 , 36 , 37 ] ( Figure 3 , Table 3 ).
Figure 3 Forest Plot analysis of Apa 1 polymorphism.
…”
Section: Resultsmentioning
confidence: 97%